A comparative evaluation of four restorative materials to support undermined occlusal enamel of permanent teeth - Prabhakar A; Thejokrishna P; Kurthukoti A (Wolters Kluwer Medknow Publications, 2006)
The purpose of this study was to test the support to undermined occlusal enamel provided by posterior restorative composite (FiltekTM P60, 3M Dental products USA), polyacid modified resin composite (F2000 compomer, 3M Dental products, USA.), radiopaque silver alloy-glass ionomer cement (Miracle Mix. GC Corp, Tokyo, Japan) and Glass Ionomer cement (Fuji IX GP). To test each material, 20 human permanent mandibular third molars were selected. The lingual cusps were removed and the dentin supporting the facial cusps was cut away, leaving a shell of enamel. Each group of prepared teeth was restored using the materials according to the manufacturer′s instructions. All the specimens were thermocycled (250 cycles, 6°C- 60°C, dwell time 30 seconds) and then mounted on an acrylic base. Specimens were loaded evenly across the cusp tips at a crosshead speed of 5 mm /minute in Hounsfield universal testing machine until fracture occurred. Data obtained was analyzed using analysis of variance and Studentized- Newman- Keul′s range test. No significant differences were detected in the support provided by P-60, F 2000, Miracle Mix or Fuji IX GP groups. The support provided to undermined occlusal enamel by these materials was intermediate between no support and that provided by sound dentin. Without further development in dental material technology and evidence of its efficacy, restorative materials should not be relied upon to support undermined occlusal enamel to a level comparable to that provided by sound dentin.